2020
DOI: 10.3390/nano10050972
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Effects of Pore Size Distribution on the Flowing Behavior of Carbonate Rocks: Linking a Nano-Based Enhanced Oil Recovery Method to Rock Typing

Abstract: As a fixed reservoir rock property, pore throat size distribution (PSD) is known to affect the distribution of reservoir fluid saturation strongly. This study aims to investigate the relations between the PSD and the oil–water relative permeabilities of reservoir rock with a focus on the efficiency of surfactant–nanofluid flooding as an enhanced oil recovery (EOR) technique. For this purpose, mercury injection capillary pressure (MICP) tests were conducted on two core plugs with similar rock types (in respect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…Studies on the application of nanoparticles for enhancement of conformance conrol in EOR operations has been reported in the literature as well. The effect of nanoparticles with various chemistry on stability and rheology of acrylamide sodium acrylate copolymer/chromium (III) acetate gel for the purpsoe of conformance control in EOR operations were investigated [ 50 ]. Synthesis of multipurpose terpolymers based on styrene, tert -butyl methacrylate, and glycidyl methacrylate and their modification non-covalent functionalization of carbon nanotubes is reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the application of nanoparticles for enhancement of conformance conrol in EOR operations has been reported in the literature as well. The effect of nanoparticles with various chemistry on stability and rheology of acrylamide sodium acrylate copolymer/chromium (III) acetate gel for the purpsoe of conformance control in EOR operations were investigated [ 50 ]. Synthesis of multipurpose terpolymers based on styrene, tert -butyl methacrylate, and glycidyl methacrylate and their modification non-covalent functionalization of carbon nanotubes is reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Rueda et al [ 31 ] showed a beneficial and negative effect on the oil recovery factor when adding SiO 2 nanoparticles to the Xanthan gum and Scleroglucan biopolymers, respectively. The article [ 32 ] presents an analysis of the effect of the pore size distribution on the flow in the carbonate rock. It was shown that using SiO 2 nanoparticle solutions with anionic surfactant improves oil recovery factor from a core with an inhomogeneous pore size distribution by 8.6%.…”
Section: Introductionmentioning
confidence: 99%
“…Despite several experimental and modeling investigations, there is currently no exact explanation for the impacts of nanoparticles on the rise in oil recovery during nanofluid flooding, which limits the adoption of the method in the industry. Some suggested theories for understanding the influence of nanofluids on oil extraction include surface tension-lowering techniques [ 32 , 33 , 34 , 35 ], the alteration of the porous medium’s wettability [ 36 , 37 , 38 ], and the change in viscosity [ 39 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%